Relationships between erythrocyte membrane mono- and poly- unsaturated fatty acid composition and clinical/cognitive indices in antipsychotic-free schizophrenia patients - Higuchi, Yuko; Takahashi, Tsutomu; Itoh, Hiroko; Sasabayashi, Daiki; Sumiyoshi, Tomiki; Suzuki, Michio (Frontiers in Psychiatry, 2024)
Introduction: Membrane phospholipid abnormalities are considered a pathophysiological background for schizophrenia. The aim of the study was to explore in detail the fatty acid (FA) composition in patients with antipsychotic-free schizophrenia and its association with clinical symptoms and cognitive function. Materials and methods: Erythrocyte membrane FAs were measured in 29 antipsychotic-free patients with schizophrenia (male/female = 11/18; mean [SD] age=26.7 [7.9] years) and age and sex-matched 32 healthy volunteers. Clinical symptoms and cognitive function were assessed using the Positive and Negative Syndrome Scale (PANSS), Brief Assessment of Cognition in Schizophrenia (BACS), and the Schizophrenia Cognition Rating Scale (SCoRS). Results: Eicosapentaenoic acid levels were lower in the schizophrenia group than in the healthy control group. In contrast, arachidonic acid and nervonic acid levels were higher in the schizophrenia group than in the control group. Nervonic acid levels were significantly associated with depression scores as measured by the PANSS. No FA levels were correlated with BACS score; however, oleic acid levels were significantly related to cognitive dysfunction, as measured by the SCoRS. Conclusion: These findings suggest that depressive symptoms along with cognitive dysfunction in daily living in schizophrenia may be linked to the FA composition abnormalities. Further studies will be needed to examine potential longitudinal FA changes during the course of schizophrenia as well as disease specificity.